Salt-Tolerant Bacteria Support Salinity Stress Mitigating Impact of Arbuscular Mycorrhizal Fungi in Maize (Zea mays L.) - Randa M. Zaki; Aida H. Afify; Eman H. Ashour; Ahmed M. El-Sawah (Microorganisms)
Egypt’s rapid population increase has resulted in higher water demand. It may significantly reduce the amount of water available for agriculture, increasing the chance of using saline water in agriculture. Using saline water certainly poses a major threat to maize growth and may severely affect the growth and productivity of this important crop. Therefore, the aim of this study was to isolate newly native salt-tolerant bacteria from Egyptian saline soils and assess their ability to produce growth-promoting substances under salinity stress, as well as test the mitigating impact of these isolated salt-tolerant bacteria along with arbuscular mycorrhizal fungi (AMF) in maize plants under salinity stress. We isolated ninety-seven salt-tolerant bacterial isolates, and these isolates show a high ability to grow under different concentrations of NaCl. The nine most efficient isolates show a high ability to produce indole acetic acid (IAA), gibberellic acid (GA), P-solubilized exopolysaccharides (EPS), proline, and antioxidants under different NaCl concentrations. Using the 16S rRNA gene, the most effective isolate STB 89 was identified, and its impact, along with AMF, on the growth of salinity-stressed maize was tested in a pot experiment. Our results showed that the growth parameters (shoot length, root length, dry weight, and leaf area), photosynthetic-related pigments (Chlorophyll a, b, and carotenoids), NPK content, and antioxidant enzymes (PPO, POX, and CAT) were improved significantly at p ≤ 0.05 due to the bioinoculant applications, while reduced proline accumulation, Na uptake, and the Na+/K+ ratio in maize plant tissues were observed compared to the control plants. Moreover, the indices of AMF colonization in maize roots and the count of bacteria in the rhizosphere were enhanced due to the bioinoculant applications under salinity stress. In addition, we found that the combined application was more pronounced than the individual application impact. Hence, our results recommended that salt-tolerant bacteria (STB 89) could support salinity, mitigating the impact of AMF in maize plants, as well as allowing better practical techniques for maize cultivation and soil sustainability under salinity stress.